EVALUASI ASET FISIK DAN FASILITAS PADA UPT BLK PEMERINTAH KABUPATEN GARUT - Nurlaila Fadjarwati; Jaka Sastrawan; Rima Midiyanti; Septian Ahmad (Pondasi, 2021)
UPT BLK is an institution formed by the Government of Garut Regency with the main task of improving the quality and quantity of the workforce. The implementation of operational activities at UPT BLK is supported by physical assets and facilities that support the implementation of training activities for participants. Physical assets and facilities that are generally in the training center include buildings, classrooms, staff rooms, practice rooms, health rooms and others. The purpose of this study was to measure the manager's perception of the performance of physical assets and facilities of the UPT BLK of the Garut Regency Government. The indicator used is a checklist of physical assets and facilities indicators which have been translated into Indonesian. This study uses a qualitative and quantitative approach with an explanatory descriptive method. Data collection techniques used are scientific observation, interviews, questionnaires and documentation studies. The results of the study indicate that the quality of physical assets and facilities in general is still relatively low. Therefore, the UPT BLK manager must pay attention to the development of physical assets and institutional facilities that are safe, clean and conducive so as to improve the training environment towards a more effective process.